Respon Siswa terhadap LKS Fisika Berbasis Contextual Teaching and Learning Materi Suhu dan Kalor - Inda Anggun Restu; Tri Ariani; Wahyu Arini (SPEJ (Science and Physic Education Journal), 2021)
Abstract: The purpose of this study was to determine the validity and students' responses to the physics worksheets based on Contextual Teaching and Learning on temperature and heat materials in-state high school students 6 Lubuklinggau. The design of this study refers to the research design of the 4-D Four-D model development (Define, Design, Develop, and Disseminate). The research subjects were class XI IPA 2 SMA Negeri 6 Lubuklinggau through purposive sampling technique. In this study, research data were obtained from validity questionnaires, and student response questionnaires and data analysis was carried out to see and observe the problems that existed at SMA Negeri 6 Lubukliggau in learning related to the use of physics worksheets based on Contextual Teaching and Learning on temperature and heat materials. Based on the study results, it was shown that the validity and response of the physics worksheets based on Contextual Teaching and Learning material on temperature and heat in students of SMA Negeri 6 Lubuklinggau. The questionnaire responses of 6 students obtained a score of 35.83 with a category strongly agree. The results of the questionnaire responses of teachers and students got a score of 36.2 with a type strongly agree. In conclusion, the physics worksheets based on Contextual Teaching and Learning Materials on Temperature and Heat in Class XI Students of SMA Negeri 6 Lubuklinggau have been valid and practical. Keywords: Physics LKS Based on Contextual Teaching and Learning, Response